Effect of the Met148Leu mutation on the structure and dynamics of the rusticyanin protein from Acidithiobacillus sp. FJ2. Issue 11 (24th July 2021) - Jafarpour, Roghayeh; Fatemi, Faezeh; Eidi, Akram; Mehrnejad, Faramarz
Abstract: The rusticyanin protein, a blue monomeric copper protein type-1, is one of the main components in the iron-electron transfer chain of the Acidithiobacillus ferrooxidans, and is the product of the rus gene expression. Herein, first the bacterial DNA of Acidithiobacillus sp. FJ2 was extracted. Then, the rus gene sequence and the sequence amino acid rusticyanin protein were determined. The Met148Leu mutation increased the oxidase activity of the rusticyanin protein, thereby enhancing the efficiency of the bioleaching process by bacteria Acidithiobacillus ferroxidans . Met148Leu mutation was created in the rusticyanin protein, then molecular dynamics (MD) simulations and structural analysis were performed. The MD analysis of the wild-type and mutant protein demonstrated a slight instability in the mutant protein and significant instability in the active site of the mutant protein. The usefulness of this study is the genetic manipulation of the native Acidithiobacillus sp. FJ2 bacterium, which can boost the bioleaching efficiency of the bacterium to some extent, and investigating its effects on the structure of a mutant protein using computational methods. Graphical Abstract: UF0001 Communicated by Ramaswamy H. Sarma